The Effects of Warfarin on the Pharmacokinetics of Senkyunolide I in a Rat Model of Biliary Drainage After Administration of Chuanxiong - Li, Haigang; Jiang, Yu; Wang, Yang; Lv, Huiying; Xie, Haitang; Yang, Guoping; Guo, Chengxian; Tang, Jing; Tang, Tao (Frontiers in Pharmacology, 2018)
The aim of this study was to elucidate the effects of warfarin on senkyunolide I in a rat model of biliary drainage after oral administration Chuanxiong extract based on pharmacokinetics. Thirty-two rats were randomly divided into four groups: CN, healthy rats after a single administration of Chuanxiong; CO, rats with biliary drainage after a single administration of Chuanxiong; WCN, healthy rats after the administration of Chuanxiong and warfarin; WCO, rats with biliary drainage after the administration of Chuanxiong and warfarin. A series of blood samples were collected at different time points before and after oral administration. An ultra-performance liquid chromatography coupled to tandem mass spectrometry (UPLC-MS/MS) method for quantification of the main components of Chuanxiong and methyclothiazide (internal standard) have been established. Comparisons between groups were performed according to the main pharmacokinetics parameters calculated by the DAS 2.1.1 software. The pharmacokinetics parameters of senkyunolide I showed a significant difference between the CN and CO groups, the AUC0-t, and Cmax of CO group increased by 5.45, 4.02 folds, respectively. There was a significant difference between the WCO and WCN groups, the Tmax of WCO group prolonged 67%; compared to the CN group, the AUC0-t, and Cmax of WCN group raised 4.84, 3.49 folds, respectively; the Tmax and Cmax between the CO and WCO groups also showed a significant difference. The operation of biliary drainage significantly affected the senkyunolide I disposition, and warfarin markedly influenced the disposition of senkyunolide I partly due to its enterohepatic circulation process in rat plasma after oral administration of Chuanxiong.